Dexmedetomidine in medical cardiac intensive care units. Data from a multicenter prospective registry. (1st July 2020) - Mateos Gaitan, Roberto; Vicent, Lourdes; Rodriguez-Queralto, Oriol; Lopez-de-Sa, Esteban; Elorriaga, Ane; Pastor, Gemma; Bañeras, Jordi; Lorenzo, Beatriz; García-Rubira, Juan Carlos; Corbi, Miguel; Ariza, Albert; Martínez-Sellés, Manuel
Abstract: Background: Dexmedetomidine induces cooperative and arousable sedation. Our aim was to analyze dexmedetomidine use in medical cardiac intensive care units (CICU). Methods: Multicenter prospective registry of patients treated with dexmedetomidine in CICU. Consecutive inclusion during a 12-month period. Results: A total of 410 patients were included, mean age was 67.4 ± 13.9 years, and 94 (22.9%) were women. Before using dexmedetomidine, 247 patients (60.2%) had delirium, 48 developed delirium after dexmedetomidine use. In 178 (43.4%) dexmedetomidine was used during weaning from mechanical ventilation, with a reintubation rate of 10.1%, early reintubation rate (<24 h) 1.7%. Seventy-seven patients (18.8%) died during admission. Dexmedetomidine mean dose infusion was 0.51 ± 0.25 μ/kg/h, during a median of 34 h (interquartile range 12–78 h). Three hundred forty-eight patients received adjuvant sedatives (84.9%). Sixty-eight patients (16.6%) had adverse effects. The most frequent adverse effects were hypotension with systolic blood pressure <80 mmHg (44 patients - 10.7%), bradycardia <40 beats per minute (15 patients - 3.7%), and both bradycardia and hypotension (4 patients - 1.0%). Patients with adverse effects received more frequently inotropes (53 [81.6%] vs. 212 [65.4%], p = 0.02) and fewer adjuvant sedatives (49 [75.4%] vs. 282 [87.0%], p = 0.01). The independent predictors of adverse effects were inotropes use (odds ratio [OR] 2.73, 95% confidence interval [CI] 1.30-5.74, p = 0.008) and lack of adjuvant sedatives (OR 3.03, 95% CI 1.49–6.26, p = 0.002). Conclusion: Dexmedetomidine safety for medical CICU patients seems to be similar to that for general intensive care unit patients. Inotropes and lack of adjuvant sedatives were associated with adverse effects. Highlights: Dexmedetomidine induces cooperative and arousable sedation, with reported benefits as sedative for surgical procedures. Evidence about dexmedetomidine in critically ill cardiac patients is lower than in patients with other conditions. Our data suggest that dexmedetomidine in cardiac intensive care units is as safety as in intensive care units. Inotropes and lack of adjuvant sedatives were associated with adverse effects in patients treated with dexmedetomidine.